Exendin‐4 and Liraglutide Attenuate Glucose Toxicity‐Induced Cardiac Injury through mTOR/ULK1‐Dependent Autophagy - Wei Yu; Wenliang Zha; Jun Ren (2018)
Mitochondrial injury and defective autophagy are common in diabetic cardiomyopathy. Recent evidence supports benefits of glucagon-like peptide-1 (GLP-1) agonists exendin-4 (Exe) and liraglutide (LIRA) against diabetic cardiomyopathy. This study was designed to examine the effect of Exe and LIRA on glucose-induced cardiomyocyte and mitochondrial injury, oxidative stress, apoptosis, and autophagy change. Cardiomyocytes isolated from adult mice and H9c2 myoblast cells were exposed to high glucose (HG, 33 mM) with or without Exe or LIRA. Cardiac contractile properties were assessed including peak shortening, maximal velocity of shortening/relengthening (±dL/dt), time to PS, and time-to-90% relengthening (TR90). Superoxide levels, apoptotic proteins such as cleaved caspase-3, Bax, and Bcl-2, and autophagy proteins including Atg5, p62, Beclin-1, LC3B, and mTOR/ULK1 were evaluated using Western blot. Mitochondrial membrane potential (MMP) changes were assessed using JC-1, and autophagosomes were determined using GFP-LC3. Cardiomyocyte exposure to HG exhibited prolonged TR90 associated with significantly decreased PS and ±dL/dt, the effects of which were partly restored by GLP-1 agonists, the effects of which were negated by the mTOR activator 3BDO. H9c2 cell exposure to HG showed increased intracellular ROS, apoptosis, MMP loss, dampened autophagy, and elevated p-mTOR and p-ULK1, the effects of which were nullified by the GLP-1 agonists. These results suggested that GLP-1 agonists rescued glucose toxicity likely through induction of mTOR-dependent autophagy.